«Great Eurasia»: interests and possibilities of Russia at interaction with China - Elena M. Kuzmina (Проблемы постсоветского пространства)
The Author analyzes the regulatory structure proposed by the President Putin’s strategy of «Great Eurasia» in Russian ofﬁcial and economic policy frameworks and development programmes, Examines internal and external factors affecting the Eurasian Union, as a base for building relationships within the «Great Eurasia». The emphasis the author makes the EAEU’s interest in the development of economic relations with the countries of «Great Eurasia» with the use of the Union. He also analyzes the dynamics of the negotiation process for conclusion of trade and economic agreements between the EEC and China and the challenges and opportunities of member countries in economic relations with China. Considered the level of compatibility of the Eurasian Union and the initiative «One belt and one road». A separate part of the article devoted to economic cooperation of Russia and China and their possible interaction in the construction of the Grand Eurasia.